Atomistic studies of shock-induced plasticity and phase transition in iron-based single crystal with edge dislocation. (March 2019) - Huang, Yongfeng; Xiong, Yongnan; Li, Pan; Li, Xiaofan; Xiao, Shifang; Deng, Huiqiu; Zhu, Wenjun; Hu, Wangyu
Abstract: In engineering applications, various types of defects inevitably exist in materials which would critically affect their properties. By introducing an edge dislocation into the model of single-crystal iron, the plasticity and α → ε phase transition in iron under shock loading have been investigated by means of non-equilibrium molecular dynamics (NEMD) simulations with a modified analytic embedded-atom model potential. Plastic slip is clearly observed in our work, which is induced by the initial edge dislocation under shock loading. The activated slip systems are considered as {110}<111> at the nucleation stage of dislocation generation, and then a self-adaptive transformation process occurs, which results in transforming the activated slip systems from {110}<111> into {112}<111>. The α → ε phase transition only occurs after the activation of dislocation slip, which indicates there is a strong connection between plasticity and the phase transition. The process of this plasticity-controlled phase transition is illustrated. By calculating the resolved shear stress along the shuffle plane of the shocked crystal iron at different moments, the mechanism of the plasticity-controlled phase transition is deeply discussed. Our findings could contribute to the better understanding of the behaviors of iron or iron-based alloy under high pressure conditions. Graphical abstract: Image 1 Highlights: Pre-existing edge dislocation can be a source for launching the new dislocations under shock loading. The transformation of the activated slip system from {110}<111> into {112}<111> is detected. Plasticity controls the α → ε phase transition by changing the resolved shear stress along the shuffle plane.